Application of Natural Kaolin as Support for the Immobilization of Catalase from Bovine Liver - Savran, Ali; Alkan, Salih; Demir, Halit; Ceylan, Hasan (Asian Journal of Chemistry, 2010)
Catalase from bovine liver was immobilized on to natural kaolin by physical adsorption method. About 80% of the protein content was immobilized on to support. The activities of immobilized catalase were determined in the reaction mixture containing substrate hydrogen peroxide and free catalase. The effects of reaction temperature, thermostability, stability in organic solvent, leaching and storage studies of immobilized catalase were investigated. Kaolin-immobilized catalase exhibited activities higher by four folds than free catalase after thermal stability test at 70ºC. Immobilized catalase was found to be stable in hexane at room temperature up to 12 d and also showed higher stability than free catalase in the storage study. Leaching studies showed that the immobilized catalase remained fully active even after being washed by 20 mL of solvent. The experimental results showed that physical adsorption is suitable for the attachment of enzyme on to kaolin.